2018
DOI: 10.4049/jimmunol.1700778
|View full text |Cite
|
Sign up to set email alerts
|

Netting Neutrophils Activate Autoreactive B Cells in Lupus

Abstract: Lupus erythematosus (LE) patients develop autoantibodies that form circulating immune complexes (ICs) with extracellular self-nucleic acids. These ICs are deposited into peripheral tissues, where they trigger detrimental organ inflammation. Recent evidence suggests that ICs contain LL37-DNA complexes derived from neutrophil extracellular traps (NETs) and that LE patients develop pathogenic autoantibodies against these structures, including Abs to LL37. However, the mechanism that leads to the generation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 37 publications
3
138
0
2
Order By: Relevance
“…Furthermore, the autoantibodies against ADAMTS‐L5 or LL‐37 could be used as biomarkers to discriminate PsA from non‐PsA. Moreover, results of a very recent study suggested that the neutrophil extracellular trap (NET)–derived DNA–LL–37 complex could activate autoreactive B cells, leading to anti–LL‐37/anti‐NET autoantibody production in lupus . It would be intriguing in future studies to test whether the autoantibody (e.g., anti–LL‐37) production in psoriasis might be mediated via the activation of autoreactive B cells through NETosis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the autoantibodies against ADAMTS‐L5 or LL‐37 could be used as biomarkers to discriminate PsA from non‐PsA. Moreover, results of a very recent study suggested that the neutrophil extracellular trap (NET)–derived DNA–LL–37 complex could activate autoreactive B cells, leading to anti–LL‐37/anti‐NET autoantibody production in lupus . It would be intriguing in future studies to test whether the autoantibody (e.g., anti–LL‐37) production in psoriasis might be mediated via the activation of autoreactive B cells through NETosis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…NETs containing cathelicidin LL-37-DNA complexes can directly trigger human memory B cells and induce the production of anti-neutrophil and anti-LL-37 antibodies in B cells of SLE patients (Fig. 1) 77 .…”
Section: Nets In Systemic Lupus Erythematosusmentioning
confidence: 99%
“…In clinical studies, we and others have demonstrated that excessive NET formation or impaired NET degradation is present both in patients with active AAV and in patients with severe SLE , and this is correlated with the severity of disease activity. Thus, preclinical and clinical studies have demonstrated an important role for NETs in the pathogenesis of both AAV and SLE.…”
Section: Introductionmentioning
confidence: 83%
“…NET‐derived DNA complexed with danger‐associated molecular patterns, such as LL‐37 or high mobility group box chromosomal protein 1 (HMGB‐1) , converts the NET DNA to potent immunogenic structures . Indeed, NETs were demonstrated to activate plasmacytoid dendritic cells and autoreactive B cells in vitro , which resulted in the production of interferon‐α (IFNα) and autoantibodies, respectively. Furthermore, NETs also have direct cytotoxic effects on (glomerular) endothelial cells , mediated by histones and MPO , which, in a murine model, was found to lead to severe, crescentic GN .…”
Section: Introductionmentioning
confidence: 99%